Assessment 2007: Oil and Gas Activities in the Arctic - Effects and Potential Effects. Volume 1. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2010)
"This assessment report details the results of the 2007 Assessment of Oil and Gas Activities in the Arctic conducted under the auspices of the Arctic Council and coordinated by the Arctic Monitoring and Assessment Programme (AMAP). It provide the accessible scientific basis and validation for the statements and recommendations made in the report 'Arctic Oil and Has 2007' that was delivered to Arctic Council Ministers in April 2008. It includes extensive background data and references to the scientific literature, and details the sources for figures reproduced in the 'Arctic Oil and Gas 2007' report. Whereas the ' Arctic Oil and Gas 2007' report contains recommendations that specifically focus on actions aimed at improving the Arctic environment, the conclusions and recommendations presented in this report also cover issues of a more specific nature, such as proposals for filling gaps in knowledge, and recommendations relevant to future monitoring and research work, etc." Canada, Denmark, Norway, United States, Nordic Council of Ministers.